Topographic anatomy of the masseteric nerve applied to masseteric-facial transfer - Joaquín Calisto; Camila Rocha; Augusto Garrido; Camilo Prego Mujica; Oscar Jacobo (Revista Brasileira de Cirurgia Plástica, 2024)
Introduction: The masseteric nerve is used as a nerve transfer in facial reanimation surgery. Therefore, an anatomotopographic study of the approach of this nerve applied to facial reinnervation surgery was performed. The objective was to describe the anatomy of the masseteric nerve as a reference during facial reanimation surgery. Method: Data were analyzed in 15 masseteric regions belonging to adult cadavers fixed in formaldehyde. Results: In 12 cases, the nerve was positioned in relation to the posterior third of the zygomatic arch. It emerged from the mandibular notch at an average distance of 14.7 mm anterior to the condylar process and 8.8 mm from the lower border of the zygomatic arch. The relationships with the masseteric vessels were variable. Conclusion: Anatomical knowledge of the nerve is essential for its approach.